The influence of adolescents' nutrition knowledge and school food environment on adolescents' dietary behaviors in urban Ethiopia: A qualitative study - Abreham Iyassu; Arnaud Laillou; Kassahun Tilahun; Fitsum Workneh; Sinksar Mogues; Stanley Chitekwe; Kaleab Baye (Wiley, 2024)
Abstract Adolescence is a critical period of physical, cognitive, and social development that needs to be supported with healthy diets. Dietary behaviours of adolescents can be shaped by their nutrition‐literacy and their interaction with parents and peers as well as their school food environment. Therefore, the present study aimed to assess factors that influence dietary behaviours of adolescents in urban Ethiopia. Sex‐disaggregated, focused group discussions (n = 70) were conducted in 36 private and government schools (n = 12/city) among adolescents (n = 432) 15-19 years of age in Addis Ababa, Bahir Dar, and Dire Dawa. Photovoice was applied in a subgroup of participants (n = 216) to gain further insights into adolescents' perception of their school food environment. Key informant interviews were conducted among school principals (n = 36). Adolescents had a relatively good nutrition knowledge and recognised the importance of diverse diets, but misperceptions also existed. They identified fruit and vegetables as healthy foods, but their consumption was deterred by food safety concerns. The adolescents identified foods high in salt, fat, and sugar, including processed/packaged foods as unhealthy, but still consumed them frequently due to their taste, affordability, availability and accessibility in and around schools. Both undernutrition and overweight/obesity were linked to social exclusion and bullying in school. Effective behavioural change communication is required to address common misperceptions. School nutrition programs should integrate water, sanitation and hygiene programs to ensure food safety. Regulations promoting healthy eating while discouraging unhealthy dietary behaviours are vital. Interventions to make nutrient‐dense and healthy foods available, accessible, and affordable are urgently needed to improve the nutrition and health outcome of adolescents.